DESECULARIZATION AS A FACTOR OF SELF-CONSCIOUSNESS OF CIVILIZATION - Meteleva, E.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
S. Huntington raised the question of the relevance of the transformation of secularized consciousness into the space of desecularization processes. Civilized self-awareness is an indicator of the level of development of sociocultural regulators of liberal democracy and a market economy. The antinomy of secular and desecular consciousness is caused by historical necessity in the context of the growing ideology of neoliberalism. The role of secularized consciousness in the space of the scientist and humanistic orientations of mass consciousness has grown. The subversiveness and depletion of the personnel of the churches of Eastern Europe, which was due to the period of total persecution, today requires considerable time in the formation of a new spirituality of moral imperatives. The insurmountability of secular consciousness and its role in organizing the basic structures for the spread of neoliberal ideology in secular culture is obvious. The confrontation of secular and desecular consciousness is a fault line in modern civilizations. The phenomenon of faith is generally attributable to human consciousness, but is blocked by a network of atheistic propaganda and the silence about the importance of a spiritual understanding of the world. In Western Europe, as a conductor of the ideology of the values of Atlantism, the issue of desecularization is especially demanded in terms of the person's return to self-knowledge. The mass consciousness saturated with a pragmatic way of life inertially replicates the factor of ersatz religions in the pluralism of modernized denominations that elevate syncretism to the level of knowledge of truth. The multiculturalism of Western Europe has revealed the failed dialogue of civilizations, although diverse projects are supported in wide mass audiences. Desecularization has become one of the ways to fill the gap in the mass consciousness losing its identity.